Hubungan Regulasi Emosi Terhadap Tingkat Kesehatan Mental Remaja Pada Masa Pandemi Covid-19 - Durotun Nafisah; Laura Khattrine; Siti Juwariyah (Universitas Widya Husada Semarang, 2021)
The large number of patients affected by Covid-19 not only causes physical symptoms and diseases, but also has a major impact on mental health with government policies in the form of physical distancing and large scale social restrictions (PSBB) to deal with Covid-19 emotional, depressed to experience stres. Emotion regulation is ability to control and adjust the emotion that appears at the right level of intensity to actieve a goal. Mental health is an important dimensions of life, because of it, life will walk with well and seasonable. Emotion changes that occus at adolescence have big influencein teenagers life. This research has done in Glonggong village RW 002. This research is quantitative that uses cross sectional with apply in inclusion and exclusion criteria. Independent variable in this research is emotion regulation even the dependent variable is health mental level of teenagers. Then for questionnaire has done validity and reliability test. For validity test uses technic of person product moment in valid item if r score count >table r (0,0361) or score sig <5% and reliability test in this research uses cronbach alpha from the result that avolded cronbach alpha score of 0,784, because of the score bigger than >0,6 so we can conclude that questionnaire for variable of emotion regulation is reliable or consistent of using in the research. The result of research shows variable of emotion regulation to health mental level of teenagers in pandemic period of covid-19, emotion regulation to health mental level of teenagers is p value (0,018<0,05). The summary of this research is there is relation between emotion regulation to health mental level of teenagers in pandemic period of covid-19. From this research, we hpe the teenagers can give the knowledge about emotion regulation and the health mental level of teenagers will be better and the teenagers can control their emotion in order they donˈt have mental health. Keywords: Pandemic Of Covid-19, Teenagers, Emotion Regulation, Health Mental Level